Efektivitas Komunikasi Pembelajaran melalui Media Website untuk Materi Ajaran Fisika (Kasus Siswa Kelas 3 SMAN 1 Jakarta Pusat) - D. H. Purnama; M. Hubeis; K. Matindas (Institut Pertanian Bogor, 2009)
This research aimed to identify factors affecting learning communication effectivity contains of cognitive, affectiveand psychomotoric. The study was conducted in SMAN 1 Jakarta from June to August 2006. There were 80respondents of students selected through purposive sampling. The study was held to evaluate effectivity of usingInformation and Communication Technology (ICT) such website that implemented by SMAN1 since 2001 ascompetence curriculum. This research is designed by survey methode. The data is analyzed using frequencydescriptive, Chi Square and Multiple Regression continued with path analysis. The results showed that (1) sex, job ofparents and students organization activity had significant correlation to access frequency and duration ofinternet/website using,.(2) Factors affecting learning communication effectivity directly were frequency, financialavailables,and free time, and indirectly were motivation, task and application easily.